The relationship between Information Technology (IT) skills and employees’ performance in Lembaga Hasil Dalam Negeri (LHDN) Kuala Terengganu / Aina Amirah Moktar - Moktar, Aina Amirah (2013)
The purpose of this study is to investigate the relationship between Information Technology (IT) skills and employee performance. This research is trying to examine between three (3) independent variables; e-mail, spreadsheet and word processing with the employee performance. By distributing the questionnaires to Lembaga Hasil Dalam Negeri (LHDN) in Kuala Terengganu, we can find that there is correlation between all the independents variables with the independent variables. The method that these study using is reliability analysis, frequencies analysis, descriptive analysis and pearson’s correlation analysis. The outcomes of this study are; there is positive relationship between e-mail, spreadsheet and word processing with employee performance. IT skills should be study for further more. This is because we live in a digital world or technology era. But, employees still refuse or not master in IT skills, this is because among the employees that wrorks is from the Gen X. Gen X is generation who is bom between 1961 to 1981 (Appelbaum et.al., 2005). Not only that, companies now are forcing to change because of the IT drastically improve. So, the employee should learn how to utilize the IT by having the IT skills. So, it is important to all institutes; individuals and organizations, to study more about the IT skills. This study want to make sure that all institutes aware of individuals who is lacking in IT skills knowledge.